Investigation of forging process for eliminating delta ferrites in USC unites last stage blades steel 10Cr12Ni3Mo2VN. (2017) - Liu, Yazheng; Sun, Jinghong; Li, Junru; Jiang, Bo; Zhang, Chaolei
Abstract: The influence of high-temperature heating and deformation on dissolution of delta ferrites in martensitic heat-resistant steel 10Cr12Ni3Mo2VN was investigated. High-temperature heating can decrease the delta ferrites in electroslag remelting ingots. But the dissolution rate of delta ferrites always decreases with the heating time. It needs too long time to completely eliminate delta ferrites only by high-temperature heating. Deformation can significantly increase the dissolution rate of delta ferrites by promoting the occurrence of dynamic recrystallization and the formation of interior grain boundaries. A multiple multi-directional forging process was designed, which can completely eliminate the delta ferrites and get fine and uniform matrix microstructure.